2012
DOI: 10.1051/epjconf/20123506002
|View full text |Cite
|
Sign up to set email alerts
|

Observation of newh9/2andh11/2bands in187T1

Abstract: Abstract. The unfavoured signature of the rotation-aligned band associated with the prolate h 9/2 structure in 187 Tl has been identified. The deformation-aligned 11/2 − [505] band is also confirmed and extended. While the alignment properties of the 11/2 − [505] band seem to indicate that it has a similar magnitude of deformation as the prolate 186 Hg core, the signature splitting at low spin, taken together with new self-consistent calculations, suggest that it may actually be triaxial with γ ≈ −18 0 near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…On careful looking at the available decay scheme of 187 Tl [46,47] and 186 Hg [48], it was observed that there are few close-by γ-ray transition energies in their decay schemes which could possibly contaminate our 566keV gamma energy peak of our interest. In this respect 564.4 keV (23/2 − → 21/2 − ) intra-band transition from h 9/2 band and 568.5 keV (23/2 − → 19/2 − ) intra-band transition from h 11/2 band in 187 Tl and the 566.9 keV (21 − → 19 − ) transition from band 3 in 186 Hg could be the potential candidates.…”
Section: 3mentioning
confidence: 99%
“…On careful looking at the available decay scheme of 187 Tl [46,47] and 186 Hg [48], it was observed that there are few close-by γ-ray transition energies in their decay schemes which could possibly contaminate our 566keV gamma energy peak of our interest. In this respect 564.4 keV (23/2 − → 21/2 − ) intra-band transition from h 9/2 band and 568.5 keV (23/2 − → 19/2 − ) intra-band transition from h 11/2 band in 187 Tl and the 566.9 keV (21 − → 19 − ) transition from band 3 in 186 Hg could be the potential candidates.…”
Section: 3mentioning
confidence: 99%